Are there Diminishing Returns to R&D? - Jakob B. Madsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2006)
Semi-endogenous models and, to some extent, also Schumpeterian models are based on the assumption of diminishing returns to R&D. This paper shows that the null hypothesis of constant returns to R&D cannot be rejected for the OECD countries.
Keywords: O3; O4; 330; returns to R&D; endogenous growth theory; Neue Wachstumstheorie; Industrielle Forschung; Theorie